Photothermal slippery surfaces towards spatial droplet manipulation. Issue 31 (2nd August 2021) - Han, Keyu; Wang, Zubin; Heng, Liping; Jiang, Lei
Abstract : Spatial manipulation of various droplets and programmable droplet storage were achieved on a photothermal slippery surface. Abstract : Intelligent responsive slippery surfaces with adjustable wettability have considerable significance in a broad range of fundamental research and application realms including microfluidic channels, microreactions, and liquid directional-conveying devices. Although considerable progress has been made in current responsive slippery surfaces, most of them usually function under a contact-type stimulus with restricted operating conditions or constructing responsivity in the whole surface, which have difficulty in satisfying remote and flexible responsive demands in complicated practical environments. Therefore, designing slippery surfaces with a configurable wettability pattern and spatial response to remote stimuli is especially important, which remains a significant challenge. Herein, we present a photothermal ZnO–Pt–fluoroalkylsilane (FAS)–paraffin slippery surface (ZPFPSS) with sensitive light responsiveness. Owing to Pt's photothermal characteristic, the paraffin layer in the ZPFPSS switched between the solid and the liquid state under on–off irradiation. This endowed the ZPFPSS with reversible switching slippery property between the pinning state and easy-sliding state for different liquid droplets. In addition, versatile responsive pathways were designed, achieving spatial manipulation of the droplets. Meanwhile, programmable micro-droplet storage with rewritable property was also achieved on the ZPFPSS. This work provides a promising interface with responsive pathways, promoting its potential applications in rewritable functional biochips, microfluidics and water-harvesting systems.